2017
DOI: 10.4067/s0718-19572017000300006
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic conditions and marine mammals: identifying a potential relationship in the coastal region of the Mexican Central Pacific

Abstract: Resumen.-Se investigaron las condiciones oceanográficas que podrían influir en la riqueza y distribución de mamíferos marinos en costas del Pacífico Central Mexicano durante el 2011. Las observaciones de mamíferos marinos se realizaron desde dos plataformas de investigación. Se muestrearon mensualmente 6 estaciones, donde se realizaron lances de CTD hasta 100 m y se tomaron muestras de agua para determinación de nutrientes inorgánicos; y otras 15 estaciones fueron muestreadas solamente durante invierno en una … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…The observed aggregation of KW in areas close to the coast in relatively shallow waters, despite a search effort over a wide region that included offshore waters beyond the continental slope and a regional submarine trench where KW observations were null, which corresponds to patterns reported in previous KW studies in the Mexican Pacific (Esquivel, Sarti, & Fuentes, 1993; Guerrero‐Ruiz, 1997; Hamilton et al, 2009; Méraz & Sánchez‐Díaz, 2008). This aggregation of KW sightings over the continental shelf between Colima and Jalisco (Figure 1) was in an area with high primary productivity (Kono‐Martínez, Ortega‐Ortiz, Olivos‐Ortiz, Torres‐Orozco, & González‐Rodríguez, 2017), similar to those where KW are commonly present (Forney & Wade, 2006).…”
Section: Figurementioning
confidence: 89%
“…The observed aggregation of KW in areas close to the coast in relatively shallow waters, despite a search effort over a wide region that included offshore waters beyond the continental slope and a regional submarine trench where KW observations were null, which corresponds to patterns reported in previous KW studies in the Mexican Pacific (Esquivel, Sarti, & Fuentes, 1993; Guerrero‐Ruiz, 1997; Hamilton et al, 2009; Méraz & Sánchez‐Díaz, 2008). This aggregation of KW sightings over the continental shelf between Colima and Jalisco (Figure 1) was in an area with high primary productivity (Kono‐Martínez, Ortega‐Ortiz, Olivos‐Ortiz, Torres‐Orozco, & González‐Rodríguez, 2017), similar to those where KW are commonly present (Forney & Wade, 2006).…”
Section: Figurementioning
confidence: 89%
“…3) is consistent with the coastal distribution reported in previous studies (Juárez-Ruiz 2014. Such a distribution aggregating towards coastal areas could be a result of the abrupt topography of the MCP, since the narrow and irregular continental margin favors deep (De la Lanza-Espino 1991) and productive waters close to shore (Juárez-Ruiz 2014, Kono-Martínez et al 2017), where foraging activities are likely since there is no competition with other coastal cetaceans (i.e., Tursiops truncatus; García and Dawson 2003). Furthermore, studies on spotted dolphins carried out in Central and South America suggested prey availability as the main reason for their distribution and abundance patterns (Acevedo and Burkhart 1998, Cubero-Prado 1998, May-Collado 2001, García and Dawson 2003.…”
Section: Spatial Distribution and Abundancementioning
confidence: 99%
“…Independientemente de las subespecies establecidas, la alta tasa de avistamiento y la alta densidad de delfines moteados observadas en el estrato costero del PCM (Tabla 1, Fig. 3) coincide con la distribución costera reportada en investigaciones anteriores (Juárez-Ruiz 2014, Kono-Martínez et al 2017). Dicha distribución agregada hacia la zona costera podría ser resultado de la topografía abrupta del PCM, debido a su estrecha e irregular plataforma continental que favorece aguas profundas (De la Lanza-Espino 1991) y productivas cerca de la costa (Juárez-Ruiz 2014, Kono-Martínez et al 2017), donde las actividades de forrajeo podrían ser probables ya que no hay competencia de otros cetáceos costeros (i.e., Tursiops truncatus; García y Dawson 2003).…”
Section: Distribución Espacial Y Abundanciaunclassified
See 2 more Smart Citations